If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 4 = -6x + 14 Reorder the terms: 4 + -2x = -6x + 14 Reorder the terms: 4 + -2x = 14 + -6x Solving 4 + -2x = 14 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 4 + -2x + 6x = 14 + -6x + 6x Combine like terms: -2x + 6x = 4x 4 + 4x = 14 + -6x + 6x Combine like terms: -6x + 6x = 0 4 + 4x = 14 + 0 4 + 4x = 14 Add '-4' to each side of the equation. 4 + -4 + 4x = 14 + -4 Combine like terms: 4 + -4 = 0 0 + 4x = 14 + -4 4x = 14 + -4 Combine like terms: 14 + -4 = 10 4x = 10 Divide each side by '4'. x = 2.5 Simplifying x = 2.5
| 7x-(2x-12)=-80 | | 15+4a-4= | | 6(ab+ab)-3ab= | | 20t^2-61t+36=0 | | log(5)y=4 | | a-40=14 | | 5x^2-25x=-30 | | 6(ab+ab)-3abn= | | log(2)128=x | | 9x-3x+90=9x+60 | | 5(-3)+4y=9 | | 0=x^5+4x^3-5x+2 | | 36-w=184 | | 5*42= | | Y=cos(2x) | | 6(20+5)= | | 5x+1y=4 | | f(0)=x^5+4x^3-5x+2 | | 20(x+2)+x= | | 9*x=495 | | 11=a-3.7 | | .35x-20=2.4+13 | | 2b+3b+8b-4b+9= | | 2x+x^2=99 | | 8x-2=-9*7x | | 10y-90=7y+100 | | 4x+2=2-(8x-7) | | -3t+9=-22 | | Cos-2sin*cos=0 | | 5(1+4Y)=9 | | 7d(3+7)= | | Cosx-2*sinx*cos*x=0 |